Risk factors of pan-vascular diseases and their interactions - Wei Shulin; Zhou Yongwen; Xu Suowen; Weng Jianping (生物医学转化)
Over the past 3 decades, with the exacerbation of population aging and lifestyle changes in China, the incidence of pan-vascular diseases, primarily characterized by atherosclerosis (AS), has been rising annually. This condition has become one of the leading causes of death among Chinese residents. Traditional risk factors affecting vascular health include hypertension, hyperglycemia, hyperlipidemia, hyperuricemia, smoking and high body mass index (BMI). An increasing number of studies have found that novel risk factors, such as microplastics, environmental pollution, unhealthy diets, psychological stress, and traffic noise also pose risks to vascular health and interactively promote the occurrence and development of pan-vascular disease. By elucidating the independent or shared pathogenic mechanisms of multiple risk factors, this review summarizes the important evidence for early intervention, comprehensive management, muti-targeted therapies, and ultimately the reduction or delay of the occurrence and pregression of pan-vascular disease.